Bio-tribological properties and cytocompatibility of Ti–Si–N coatings. (May 2015) - Zhang, Ming; Ma, Shengli; Xu, Kewei; Bai, Long; Chu, Paul K.
Abstract: Ti–Si–N coatings are synthesized on titanium alloy (Ti6 Al4 V) by arc-enhanced magnetron sputtering and the microstructure and tribological properties are determined. The friction coefficient of the Ti–Si–N coatings, which is smaller in human serum than ambient air, decreases gradually with Si contents. Protein gel electrophoresis shows that the small friction coefficient is due to adsorbed proteins from the human serum under sliding conditions. The cytocompatibility of the coatings is assessed in vitro by a relative nitrite assay. The Ti–Si–N coatings have a positive effect on nitric oxide synthesis on the endothelial cells. The cell morphology and spreading on the coatings are examined by fluorescence staining. The Ti–Si–N coating with 12 at% Si exhibits the best effects in promoting actin cytoskeleton formation and cell spreading compared to coatings with different Si contents and titanium alloy. Highlights: Ti–Si–N coatings improve the bio-tribological properties of implants in serum. The friction coefficients of Ti–Si–N coatings are significantly lower in serum. Ti–Si–N coating helps to reduce possibility wear debris particles. Ti–Si–N coatings can promote the endothelial cells nitric oxide synthesis.